Трансформація національних економіко-правових процесів на основі патентної охорони біотехнологічних винаходів - Андрейченко, Світлана Сергіївна; Андрейченко, С. С.; Андрейченко, Светлана Сергеевна; Andreichenko, Svitlana S.; Андрейченко, Андрій Вадимович; Андрейченко, А. В.; Андрейченко, Андрей Вадимович; Andreichenko, Andrii V.; Гарафонова, Ольга Іванівна; Гарафонова, О. І.; Гарафонова, Ольга Ивановна; Harafonova, Olha I.; et al. (Kharkiv institute SHEI «University of Banking», 2020)
Досліджено особливості патентної охорони біотехнологічних винаходів як чинника трансформації національних економіко-правових процесів. Установлено, що умови для отримання патенту на біотехнологічні винаходи відрізняються від умов патентування в інших сферах, зважаючи на те, що усі винаходи в галузі біотехнології прямо або опосередковано є продуктом природи. Акцентовано на важливості чіткого розмежування між відкриттям природного явища і новим об’єктом інтелектуальної власності. Охарактеризовано критерії патентування для винаходів у галузі біотехнології. Обґрунтовано, що однакові стандарти патентування винаходів у галузі біотехнології неможливо застосовувати в різних правових системах, тому відповідні рішення повинні ухвалюватися, виходячи з положень національного права. Установлено, що нормативно-правове регулювання патентування винаходів у галузі біотехнології потребує удосконалення з урахуванням особливостей біотехнологічних об’єктів інтелектуальної власності.

Исследованы особенности патентной охраны биотехнологических изобретений как фактора трансформации национальных экономико-правовых процессов. Установлено, что условия для получения патента на биотехнологические изобретения отличаются от условий патентования в других сферах, несмотря на то, что все изобретения в области биотехнологии прямо или косвенно являются продуктом природы. Акцентировано на важности четкого разграничения между открытием природного явления и новым объектом интеллектуальной собственности. Охарактеризованы критерии патентования для изобретений в области биотехнологии. Обосновано, что одинаковые стандарты патентования изобретений в области биотехнологии невозможно применять в различных правовых системах, поэтому соответствующие решения должны приниматься, исходя из положений национального права. Установлено, что нормативно-правовое регулирование патентования изобретений в области биотехнологии требует совершенствования с учетом особенностей биотехнологических объектов интеллектуальной собственности.

The peculiarities of patent protection of biotechnological inventions have been investigated as a factor of transformation of national economic and legal processes. It has been established that the conditions for obtaining of a patent for biotechnological inventions differ from the conditions of patenting in other spheres, since all biotechnology inventions directly or indirectly are the product of nature. It has been determined that the issue of the conformity of such inventions with the patentability conditions is a key issue when providing the intellectual property (IP) rights for biotechnological inventions. The invention in the field of biotechnology meets the requirements of patentability, provided that it is new, has an inventive level and is industrially suitable. It has been substantiated that the same standards of patenting of inventions in the field of biotechnology can not be applied in different legal systems, therefore corresponding decisions should be made on the basis of the national law. It has been established that the increase of applications submitted in Ukraine for biotechnology inventions during 2013—2017 has been ensured due to the inventive activity of foreign applicants. It has been also determined that the absence of special legislative regulation of relations related to biotechnology constrains the development of the biotechnological industry in Ukraine. The key role of the state system of legal protection of IP has been proved, since the introduction of effective IP management mechanisms and integrated support for innovators are one of the main factors of the determination of the possibility of affirmation in the global IP system.
National economic and legal processes transformation on the basis of patent protection of biotechnological inventions
Андрейченко С. С. Трансформація національних економіко-правових процесів на основі патентної охорони біотехнологічних винаходів / С. С. Андрейченко, А. В. Андрейченко, О. І. Гарафонова, В. Г. Маргасова, І. В. Балла // Financial and credit activities: problems of theory and practice. – V. 1 (32). - Kharkiv institute SHEI «University of Banking», 2020. – P. 444-452.
Keywords: біотехнології; патентування; критерії патентоспроможності; новизна; винахідницький рівень; промислова придатність; биотехнологии; патентование; критерии патентоспособности; новизна; изобретательский уровень; промышленная применимость; biotechnology; patenting; patentability criteria; novelty; inventory level; industrial suitability; Research Subject Categories::LAW/JURISPRUDENCE